Islamic values in bureaucratic practice: A case study of civil service management in East Kotawaringin Indonesia - Ahmad Hidir Amin; Khairil Anwar; Mowafg Abrahem Masuwd (Rafandha Press, 2026)
Background: Studies on the Islamization of knowledge have been widely developed within Islamic education, particularly in relation to epistemological and pedagogical frameworks. However, empirical research examining how Islamic values are integrated into the management practices of government bureaucracy remains relatively limited, especially from the perspective of Islamic educational management. Purpose: This study aims to analyse how Islamic values in knowledge are integrated into the management of the civil service (ASN) from the perspective of Islamic education management in East Kotawaringin Regency. Method: This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews with civil servants, observations of organizational activities, and analysis of policy documents related to ASN management. The data were analysed thematically through the processes of data reduction, data display, and conclusion drawing. Findings: The findings reveal that the integration of Islamic values in ASN management is reflected in leadership practices emphasizing trustworthiness and responsibility, the development of civil servant competencies based on Islamic work ethics, and the formation of organizational culture through spiritual guidance activities in the workplace. However, the internalization of religious values within bureaucratic governance remains largely normative and has not been fully institutionalized in organizational management mechanisms such as performance evaluation systems, organizational regulations, and bureaucratic accountability frameworks. These findings indicate a gap between the discourse of religious values in bureaucratic leadership and their structural implementation in governance systems.